Can salesperson guilt lead to more satisfied customers? Findings from India - Gabler, Colin B. (2017)
Purpose The purpose of this paper is to investigate guilt proneness as a prosocial salesperson trait and its impact on outcomes important to the firm, the customer as well as the salesperson. Specifically, the authors look at how this variable relates to job effort and the indirect effects on customer satisfaction. The corollary purpose is to uncover how managers influence these constructs through positive outcome feedback. Design/methodology/approach Prosocial motivation theory grounds the conceptual model which the authors test through survey implementation. The final sample consisted of 129 business-to-business (B2B) salespeople working across multiple industries in India. Latent moderated structural equation modeling was utilized to test the proposed model. Findings The results suggest that guilt proneness positively influences the likelihood that a salesperson adopts a relational orientation, which has a direct effect on individual effort and an indirect effect on customer satisfaction. Supervisors have the ability to amplify this effort through positive outcome feedback, but only when relational orientation is low. Their support had no effect on salespeople with a high relational orientation. Originality/value The study is unique in that it combines an overlooked prosocial trait with a B2B Indian dataset. We provide value for firms because our results show that guilt-prone salespeople put more effort into their job – ”something universally desirable among sales managers” – through the development of a relational orientation. The authors also give practical implications on how to support salespeople given their level of relational orientation.